Efektivitas Board Game sebagai Media Pembelajaran dalam Meningkatkan Student Engagement Siswa: Studi Literatur - Wijaya, Tsamara Ghinah Salsabilah; Wahyuni, Sri; Mudakir, Imam; Wahono, Bevo; Wicaksono, Iwan (PAKAR Pendidikan, 2023)
The use of game mechanics, game aesthetics, and game thinking can engage a person to be motivated to improve learning and solve problems. Students' motivation to learn when using games increases because in the game students feel happy and the learning that is carried out becomes cooperative. Game-based learning allows students to develop problem-solving skills, cooperate with peers and better communicate knowledge and learning outcomes. Students' understanding using games is considered easier to remember because learning is more fun. The results of this study found that there is a positive relationship between student engagement and the use of games in classroom learning. This positive relationship is seen in the use of games that increase students' emotional state such as excitement and motivation. This in turn improves student learning outcomes, as students become actively engaged in learning.